Electronic whiskers for velocity sensing based on the liquid metal hysteresis effect. Issue 48 (2nd December 2022) - Sun, Xinlong; Fu, Jun-Heng; Zhao, Hongbin; Xiang, Wentao; Zhan, Fei; Sun, Chenkun; Tang, Shousheng; Wang, Lei; Liu, Jing
Abstract : In the bending process, the hysteresis of the liquid metal in the fiber induces the decline of current, which could effectively detect the motion speed. Abstract : The artificial biomimetic sensory hair as state-of-art electronics has drawn great attention from academic theorists of industrial production given its potential application in soft robotics, environmental exploration and health monitoring. However, it still remains a challenge to develop highly sensitive electronic sensory hair with fast response. In this study, a bio-inspired electronic whisker (e-whisker) with a hollow polymer shell and a liquid metal core was prepared by microinjection for airflow measurement and detection of obstacles. In addition, we illustrated the effect of liquid metal hysteresis on its distribution in microchannels on deformation. The difference in the deformed velocity between the selected fiber and EGaIn would result in a disturbance emerging in the liquid metal channel, which further causes a variation in resistance. Taking advantage of this phenomenon, the integrated fiber e-whisker can be employed to detect tiny airflow and disturbance. The experimental results indicate that the fiber sensor can detect the airflow velocity as low as 0.2 m s −1 within 0.1 s. The e-whisker can accurately monitor rainfall, human motion and object velocity. This work sheds light on the liquid metal viscosity-induced sensing mechanism and offers a novel strategy to fabricate high-performance velocity sensors.